A multi-layer bioinspired design with evolution of shish-kebab structures induced by controlled periodical shear field - J. Zhang; K. J. Liu; H. Liu; X. Y. Qian; Y. Zhang; T. Wang; K. Z. Shen (eXPRESS Polymer Letters)
The crystallization of polymers, caused by flow fields in the melt, has been the subject of extensive studies for many years. In this study, we use periodical shear to induce polypropylene to form multi-layer structure, which is usually observed in plants. Two interesting points were found: firstly, the quest of mimicking natural structures was achieved by controlled periodical shear field; secondly, the evolution from nano to shish-kebab-like cylindrite structure was obtained in the multi-layer structure, which can be clarified by nuclei competition model. This study can be used to better understand the shear-induced crystallization of polymer. Here our intention is to place this new observation on the map, leaving a fuller presentation and discussion of the work to a future publication.